Job Opportunities in Material(s) Technology - Saifful Kamaluddin, Muzakir; Sutjipto, A. G. E.; Muhammad Hafiz, Mazwir; Mohamad Ashry, Jusoh; Farah Hanani, Zulkifli (Institute of Materials Malaysia, 2017)
Materials are substances of universe which have properties that make them useful in structures, machines, devices, products, and systems. There are three closely connected areas of study related to materials, namely material(s) technology, materials engineering and materials science. Material(s) technology is a relatively comprehensive discipline that begins with the production of goods from raw materials to processing of materials into the shapes and forms needed for specific applications. Material(s) technologists work with materials such as metals, plastics, rubbers and ceramics. They study how the composition, structure, processing, and application of these materials, are inter-related.